The strange case of Jane O. : a novel [large type] - Walker, Karen Thompson (Random House Large Print, 2025)
"A woman born with perfect memory suddenly develops a series of eerie psychological symptoms--blackouts, hallucinations, premonitions, an inexplicable sense of dread. It is the first year after her child is born, and she and her untraditional psychiatrist struggle to solve the mystery of what is happening to Jane, to her mind. Then Jane suddenly goes missing and is found a day later lying unconscious in Brooklyn's Prospect Park, with no memory of her missing hours. A police detective becomes suspicious of Jane, and begins to track her, convinced that Jane is lying. What happened to Jane, and what do these peculiar experiences, including in something called a fugue state, have to do with a hallucination Jane has about a young man she knew twenty years ago, who warns her of a disaster ahead?"--